2004
DOI: 10.4049/jimmunol.172.11.7095
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Receptor Develops Airway Hyperresponsiveness Independently of Airway Inflammation in a Murine Asthma Model

Abstract: Lipid mediators play an important role in modulating inflammatory responses. Platelet-activating factor (PAF) is a potent proinflammatory phospholipid with eosinophil chemotactic activity in vitro and in vivo. We show in this study that mice deficient in PAF receptor exhibited significantly reduced airway hyperresponsiveness to muscarinic cholinergic stimulation in an asthma model. However, PAF receptor-deficient mice developed an eosinophilic inflammatory response at a comparable level to that of wild-type mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Several reports have used PAFR-KO mice to elucidate the role of PAF in various pathophysiologies. The PAFR-KO mice exhibited attenuation in animal models in which inflammatory injuries were crucial: chemical lung injury, 18 bronchial asthma, 19 and sponge-induced subcutaneous granuloma formation. 20 On the other hand, PAFR-KO mice showed exacerbation of infection models such as pulmonary gramnegative bacteria infection 41 and cardiac Trypanosoma infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have used PAFR-KO mice to elucidate the role of PAF in various pathophysiologies. The PAFR-KO mice exhibited attenuation in animal models in which inflammatory injuries were crucial: chemical lung injury, 18 bronchial asthma, 19 and sponge-induced subcutaneous granuloma formation. 20 On the other hand, PAFR-KO mice showed exacerbation of infection models such as pulmonary gramnegative bacteria infection 41 and cardiac Trypanosoma infection.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Therefore, we have developed genetically engineered PAFR-deficient (PAFR-KO) mice to confirm the role of PAF in vivo. 17 The resultant PAFR-KO mice exhibit attenuated symptoms in several animal models such as chemical lung injury, 18 bronchial asthma, 19 and sponge-induced subcutaneous granuloma formation. 20 It has been demonstrated that infiltrating inflammatory cells play important roles in these animal models.…”
mentioning
confidence: 99%
“…Because elevated levels of LPC are observed in Krabbe and twitcher brain, it can be postulated that LPC may, at least in part, be responsible for the inflammatory response observed in Krabbe disease and in twitcher mice. Moreover, LPC is also a precursor for platelet-activating factor, which is a well-known inflammatory mediator in the regulation of several inflammatory diseases (60)(61)(62)(63). Therefore, inhibition of LPC generation should play an important part in therapeutics against the disease process in Krabbe disease and twitcher mice brains.…”
Section: Discussionmentioning
confidence: 99%
“…From the paraffin-embedded right and left lobes of lung, sections of 5-m thickness were prepared from the middle position of each lobe, and stained with H&E or periodic acidSchiff (PAS). A semiquantitative scoring system was used to grade the size of lung infiltrates in the H&E-stained sections, where ϩ5 signifies widespread infiltrates around the majority of vessels and bronchioles, and ϩ1 signifies a small number of inflammatory foci (30). The goblet cell hyperplasia in the PAS-stained sections was graded by a semiquantitative scoring system (0 ϭ Ͻ5% goblet cells in airway epithelium; 1 ϭ 5-25%; 2 ϭ 25-50%; 3 ϭ 50-75%; 4 ϭ Ͼ75%) as described by McMillan et al (31).…”
Section: Calcium Mobilization In Mouse Granulocytesmentioning
confidence: 99%